Fault‐tolerant distributed load/frequency supervisory strategies for networked multi‐area microgrids. (2nd January 2014) - Tedesco, Francesco; Casavola, Alessandro; Odgaard, P. F.; Aubrun, C.; Majanne, Y.
SUMMARY A distributed supervisory strategy for addressing load/frequency set‐point reconfiguration problems in networked multi‐area microgrid is presented. The aim is at finding a distributed coordination strategy able to reconfigure, whenever necessary in response to unexpected load changes and/or faults, the nominal set‐point on frequency and generated power to the generators of each area so that viable evolutions arise for the overall power system during transients and a new post‐fault sustainable equilibrium is reached. In order to demonstrate the effectiveness of the strategy, an example on a four‐area power system is presented. Copyright © 2014 John Wiley & Sons, Ltd.